2016
DOI: 10.1002/mbo3.379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human serum and apo‐Transferrin on Staphylococcus epidermidis RP62A biofilm formation

Abstract: Biofilm‐associated Staphylococcus epidermidis infections present clinically important features due to their high levels of resistance to traditional antibiotics. As a part of human innate immune system, serum shows different degrees of protection against systemic S. epidermidis infection. We investigated the ability of human serum as well as serum component to inhibit the formation of, and eradication of mature S. epidermidis biofilms. In addition, the synergistic effect of vancomycin combined with apo‐Transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…in planktonic cells/biofilm single or dual culture was significantly enhanced in the presence of 10% C‐inactivated FBS (Table ). However, Ding et al () reported that even heat‐inactivated human serum can inhibit the biofilm formation of C. albicans ; we previously reported that the complement is the main antibiofilm component against S. epidermidis in human serum (She et al ). Similar to our results, Yin et al () reported that serum from burn‐injured rats increased S. aureus biofilm formation and induced bacterial aggregation and adherence to human fibronectin and fibrinogen by elevating oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…in planktonic cells/biofilm single or dual culture was significantly enhanced in the presence of 10% C‐inactivated FBS (Table ). However, Ding et al () reported that even heat‐inactivated human serum can inhibit the biofilm formation of C. albicans ; we previously reported that the complement is the main antibiofilm component against S. epidermidis in human serum (She et al ). Similar to our results, Yin et al () reported that serum from burn‐injured rats increased S. aureus biofilm formation and induced bacterial aggregation and adherence to human fibronectin and fibrinogen by elevating oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…Biofilm production is a way by which bacteria protect themselves from the host immune system (She et al., ). However, whether rstA and rstB take part in biofilm formation remains undefined.…”
Section: Discussionmentioning
confidence: 99%
“…After adhesion to its host, bacteria are possible to start the invasion, besides they should try to protect themselves against the host immune system during this process. Therefore, various ways were developed, such as biofilm production (Atwood et al, 2015;Rybtke et al, 2015;She et al, 2016). Lee et al (2004) found that the oppA is involved in biofilm production of Vibrio fluvialis.…”
Section: Discussionmentioning
confidence: 99%